2016
DOI: 10.1055/s-0036-1592158
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Adverse Effects of Deep Brain Stimulation: Umbrella Review of Meta-Analyses

Abstract: Background This umbrella review summarizes the evidence across meta-analyses regarding the effectiveness and adverse effects of deep brain stimulation (DBS). Methods Databases were searched up to March 2015 for meta-analyses of comparative trials in humans assessing the effectiveness or adverse effects of DBS. Data selection, data extraction, and risk of bias assessment were performed by two independent reviewers. Results Seven eligible systematic reviews were included assessing the use of DBS for epilepsy (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Neuromodulation in the form of recurrent deep brain stimulation (DBS) (39, 40), which is not yet approved in the United States but is in Europe, appears to be more effective than vagus nerve stimulation, but rarely renders patients seizure free.…”
Section: Recent Developments In Epilepsy Surgerymentioning
confidence: 99%
“…Neuromodulation in the form of recurrent deep brain stimulation (DBS) (39, 40), which is not yet approved in the United States but is in Europe, appears to be more effective than vagus nerve stimulation, but rarely renders patients seizure free.…”
Section: Recent Developments In Epilepsy Surgerymentioning
confidence: 99%
“…49 A more rigorous review of 15 meta-analyses of DBS found that conclusions about its efficacy or comparative effectiveness cannot be drawn. 50 Because of the nature of neurosurgery, DBS has many potential complications, including cognitive changes, headache, infection, seizures, stroke, and hardware failure.…”
Section: Clinical Pointmentioning
confidence: 99%